Peran Epidemiologi dan Biomekanika dalam Mencegah Cedera HIIT untuk Atlet Basket Kota Makassar - Suwardi Suwardi; Arga Arga; Benny Badaru (Prodi Pendidikan Jasmani dan Olahraga, 2026)
High-Intensity Interval Training (HIIT) in basketball often faces high injury risks due to intensive training loads. This study aims to analyze the role of epidemiology and biomechanics in preventing HIIT injuries for basketball athletes in Makassar City. The study used a quantitative method with a quasi-experimental design on 156 basketball athletes (aged 18-25 years) for 24 weeks. Data were collected through injury surveillance using the Orchard Sports Injury Classification System and three-dimensional biomechanical analysis (240 Hz). Statistical analysis used Cox proportional hazards regression, principal component analysis, and multivariate logistic regression. Results showed an injury incidence rate of 8.7 per 1000 athlete-exposures (95% CI: 6.2-11.4) with 73.6% lower extremity injuries. Significant biomechanical factors included peak knee valgus angle (HR=2.34; p<0.001), vGRF asymmetry >15% (HR=1.87; p=0.003), and contact time <180ms (HR=1.92; p=0.002). The predictive model showed excellent discriminatory power (AUC=0.843; sensitivity=81.2%; specificity=76.5%). The novelty of this research lies in the integration of epidemiological and biomechanical approaches to identify HIIT injury risk factors in basketball athletes with effect size analysis and Self-Determination Theory framework. This approach proved effective for pre-participation screening and injury risk stratification. The practical implications of this research provide evidence-based references for coaches and sports practitioners in designing safe and effective HIIT programs for basketball athletes.